NARRATIVE TEXT SEBAGAI SUMBER BELAJAR MATA PELAJARAN BAHASA INGGRIS UNTUK MENUMBUHKAN NILAI MORAL PESERTA DIDIK - Ahmad Sarwani (LINGUA : Jurnal Bahasa, Sastra, dan Pengajarannya, 2015)
This paper describes how narrative texts are explored as the sources of values for morale development of the learners of SMP levels. Narrative texts that refer to tales or stories described in the finction versions may be written in English or in Bahasa Indonesia the teaching values in the text are relevant to the students’ level of comprehension.  Morale values from the texts are extracted into its teaching including honesty, courtesy, responsibility, perseverance, struggle, religiosity, tolerance, discipline, self-reliance, and work hard.  Selected texts are identified bybthe teacher and instructional objectives are identified in adherence to the competencies and learning outcomes.  Characterustics of good texts including authenticity, complexity of languages and vocabulary selection are crucial in the process.